1992
DOI: 10.1029/92wr01759
|View full text |Cite
|
Sign up to set email alerts
|

Field study of dispersion in a heterogeneous aquifer: 4. Investigation of adsorption and sampling bias

Abstract: The declining mass balance trend observed for bromide and three fluorobenzoate tracers during a natural gradient experiment at a site near Columbus, Mississippi, prompted investigations related to the reactivity of the tracers and the representativeness of the tracer samples obtained from multilevel samplers. A laboratory soil column study indicated that adsorption of bromide during the field experiment was of the order of 20% and that up to 10% of the three fluorobenzoates was adsorbed. The presence of iron o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
95
0
1

Year Published

1993
1993
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 119 publications
(101 citation statements)
references
References 6 publications
5
95
0
1
Order By: Relevance
“…Data from previous field investigations, as well as laboratory experiments using aquifer material collected from the study site, demonstrated a potential for the natural attenuation of hydrocarbons within the Columbus aquifer (12,(14)(15)(16)(17)(18)(19). Subsequent samples collected from the NAT study site successfully linked changes in microbial metabolic activity and community structure with exposure to hydrocarbons.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Data from previous field investigations, as well as laboratory experiments using aquifer material collected from the study site, demonstrated a potential for the natural attenuation of hydrocarbons within the Columbus aquifer (12,(14)(15)(16)(17)(18)(19). Subsequent samples collected from the NAT study site successfully linked changes in microbial metabolic activity and community structure with exposure to hydrocarbons.…”
Section: Discussionmentioning
confidence: 99%
“…Aquifer material ranges from sand (fine granular) to gravelly sand (coarse granular). Background hydrological and microbiological information have been previously described (12,(14)(15)(16)(17)(18)(19). Subsurface core samples were recovered from locations in close proximity to multilevel groundwater sampling wells and processed onsite using aseptic technique as previously described (12).…”
Section: Description Of the Study Site And Sample Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mean is porosity l n ¼ 0:20. These values are of course different from a mean lnðKÞ of À11.6 and variance of 6.6 obtained by direct-push injection logger measures (Bohling et al, 2012) and from a mean porosity of 0.31 as reported by Boggs and Adams (1992). These differences are the consequence of the data paucity assumption and they do not prevent pursuing the aims of the papers.…”
Section: Analog Site Datamentioning
confidence: 70%
“…The edge sites on clays are also reported to contain positive sites. Under low pH conditions (e.g., pH = 5), significant sorption of anionic tracers occurs in systems with high concentrations of iron oxides and kaolinite (Boggs and Adams 1992;Seaman 1998 . Because of competition, their effective sorption is minimal.…”
Section: Potential Sorption Of Anionsmentioning
confidence: 99%